Perioperative assessment of troponin level in the non-cardiac interventions: is there such a need? - A. N. Sumin (Рациональная фармакотерапия в кардиологии)
The rate of cardiac events (myocardial infarction, death) in non-cardiac surgery is about 2% to 3%. However, increase in troponin is noted much more often from 5% to 25% of patients. Such an isolated increase in troponin in the absence of criteria for myocardial infarction is also called "myocardial injury after non-cardiac surgery". This condition is associated with poor prognosis directly after surgery and in the long term. Current data on screening troponin level after surgery and proposals for the treatment of patients with elevated levels are presented. Different points of view on the issue are discussed. This allows more fully illuminating the problem and helping the clinician in treatment of these patients.